ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS V DITINJAU DARI MOTIVASI BELAJAR PADA MATERI PERKALIAN PECAHAN - Ani Nur Azizah; Yuyu Yuhana; Sukirwan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to determine the effect of problem-solving abilities on students' learning motivation on multiplication fractions in grade 5 of SDN Citangkil Baru. This research method uses a qualitative descriptive research method. Data collection techniques used are observation, interviews, tests and documentation. The research procedure consisted of four stages, namely the pre-field stage, the field work stage, the data analysis stage and the report preparation stage. The results of this study show that student motivation influences the ability to solve mathematical problems in multiplication fraction material which consists of four indicators, namely feelings of pleasure and diligent learning, willingness and interest in learning, intelligence and independence in learning and achievement in learning. And students' problem-solving abilities in terms of student learning motivation in grade 5 SDN Citangkil Baru shows the results of an average percentage score of 80. Thus it can be concluded that problem-solving abilities affect student learning motivation or student motivation is good for learning mathematics, so problem-solving abilities will be good also.